Tiberian Hebrew Phonology: Focussing on Consonant Clusters - de Caen, Vincent (Journal of Semitic studies, 2002)
Tiberian Hebrew Phonology: Focussing on Consonant Clusters Andries W.Coetzee (Studia Semitica Neerlandica 38). Van GorcumAssen 1999xiii + 215HardbackHFL 140.00 90‐232‐3431‐6 , 1University of Toronto